53rd AIAA Aerospace Sciences Meeting 2015
DOI: 10.2514/6.2015-0558
|View full text |Cite
|
Sign up to set email alerts
|

Initial Assessment of Space Launch System Transonic Unsteady Pressure Environment

Abstract: A series of wind tunnel tests were conducted at the NASA Langley Research Center Transonic Dynamics Tunnel to assess the transonic buffet environment for the Space Launch System (SLS) launch vehicle. An initial test, conducted in 2012, indicated an elevated buffet environment prompting a second test to provide further insight into the buffet phenomena and assess potential solutions to reduce the response levels of these environments. During the course of the test program, eight variants of the SLS-10000 config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…[6][7][8][9] Efforts to develop BFFs for the SLS configuration have been underway since 2011 and there have been two primary test programs conducted to obtain unsteady buffet pressures. [10][11] Buffet tests in 2012 identified high fluctuating pressure environments on the core and booster downstream of the booster forward attachment near Mach 0.92. Coupled loads analysis revealed that when preliminary BFFs developed from these environments were applied to the vehicle structure, buffet loads were largely the source of exceedances of structural and vibratory limits on the SLS vehicle.…”
mentioning
confidence: 99%
“…[6][7][8][9] Efforts to develop BFFs for the SLS configuration have been underway since 2011 and there have been two primary test programs conducted to obtain unsteady buffet pressures. [10][11] Buffet tests in 2012 identified high fluctuating pressure environments on the core and booster downstream of the booster forward attachment near Mach 0.92. Coupled loads analysis revealed that when preliminary BFFs developed from these environments were applied to the vehicle structure, buffet loads were largely the source of exceedances of structural and vibratory limits on the SLS vehicle.…”
mentioning
confidence: 99%